2014
DOI: 10.3109/19396368.2014.973123
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum anti-Müllerian hormone levels and the follicular arrest for women with polycystic ovary syndrome

Abstract: (2015) The relationship between serum anti-Müllerian hormone levels and the follicular arrest for women with polycystic ovary syndrome, Systems Biology in Reproductive Medicine, 61:2, 103-109, DOI: 10.3109/19396368.2014.973123 To link to this article: https://doi.org/10. 3109/19396368.2014 AbstractThe aim of this study was to ascertain whether higher levels of serum anti-Mü llerian hormone (AMH) are associated with the ovarian follicular arrest in women with polycystic ovary syndrome (PCOS). This prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This study revealed a significant positive correlation between AMH levels and the LH/FSH ratio in lean women with PCOS (Table 3 ). Several previous studies have reported similar findings, demonstrating a positive correlation between AMH and LH levels in women with PCOS 46 48 . In women with PCOS, there is an increased production of AMH from ovarian granulosa cells compared to controls.…”
Section: Discussionsupporting
confidence: 75%
“…This study revealed a significant positive correlation between AMH levels and the LH/FSH ratio in lean women with PCOS (Table 3 ). Several previous studies have reported similar findings, demonstrating a positive correlation between AMH and LH levels in women with PCOS 46 48 . In women with PCOS, there is an increased production of AMH from ovarian granulosa cells compared to controls.…”
Section: Discussionsupporting
confidence: 75%
“…Ultrasound was used to confirm the presence or absence of PCO in a subset of women, but data on ovarian morphology and antral follicle counts were not collected as experimental variables. Increases in per-follicle output have been observed in women with PCOS (11,41) and this, in combination with increased numbers of antral follicles, is the likely explanation for the increased total AMH levels in serum. Incorporating antral follicle counts into future multivariate predictive models may enable AMH output per follicle to be estimated (Serum [Total AMH]/Antral follicle count) and assessed as a predictive variable.…”
Section: Roc Analysismentioning
confidence: 93%
“…The minute follicles resemble cyst-like structures on transvaginal ultrasonography. [38][39][40][41][42] Initially, as authorized in the Rotterdam criteria, the cut-off value for identifying a polycystic morphology was a value of 12 or more Follicle Number Per Ovary (FNPO), measuring between the size of 2-9 mm or, an ovary with a volume of 10 cm 3 on a transvaginal scan. 26 The FNPO value, a key parameter, was later updated in conformity with the technological advancements that enabled more magnified imaging.…”
Section: Ovulatory Dysfunctionmentioning
confidence: 99%